Association between myocardial layer-specific strain and high 10-year risk of atherosclerotic cardiovascular disease in hypertension—findings from the China-PAR project study - Chen, Jianxiong; Yang, Xiaohuan; Li, Xinyi; Jin, Lin; Wu, Lingheng; Zhang, Mengjiao; Du, Lianfang; Luo, Xianghong; Li, Zhaojun (Frontiers in Cardiovascular Medicine, 2024)
Objectives: Myocardial layer-specific strain is a sensitive tool for detecting myocardial dysfunction. The objective of this study was to assess the left ventricle (LV) functional change using myocardial layer-specific strain and its relationship to 10-year atherosclerotic cardiovascular disease risk (10Y-ASCVDR) in individuals with hypertension (HP). Methods: The parameters of left ventricle (LV) structure, layer-specific global longitudinal strain (GLSww, GLSendo, GLSmid, GLSepi), and layer-specific global circumferential strain (GCSww, GCSendo, GCSmid, GCSepi) were analyzed by two-dimensional speckle tracking echocardiography in 239 hypertensive patients and 124 control group subjects. Furthermore, according to the 10Y-ASCVDR scores, the participants were divided into low-risk (LR) and high-risk (HR) subgroups. The correlation between myocardial layer-specific strain and 10Y-ASCVDR was further analyzed by the restricted cubic spline function (RCS). Results: The values of GLSww, GLSepi, GLSmid, and GLSendo were significantly lower in HP patients with HR than in HP patients with LR and controls (p <0.05). However, there were no significant differences in layer-specific GCS between the groups (p >0.05). RCS analysis showed that 10Y-ASCVDR exhibited a significant J-shaped relationship with layer-specific GLS and GCS. After adjusting for confounding factors, GLSww (β = 0.156, p = 0.042), GLSmid (β = 0.161, p = 0.032), GCSendo (β = 0.163, p = 0.024) and GCSmid (β = -0.175, p = 0.030) were identified as independent influencing factors for high 10Y-ASCVDR. Conclusions: In hypertensive patients, myocardial layer-specific strain, especially GLS, sensitively detected LV dysfunction and showed a significant J-shaped relationship with 10Y-ASCVDR. GCSmid may have a compensatory effect on myocardial impairment. LV myocardial layer-specific strain may help to understand the early compensatory mechanisms of myocardium in hypertension.